2023
DOI: 10.1002/jcb.30453
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐222‐3p suppresses C2C12 myoblast proliferation and differentiation via the inhibition of IRS‐1/PI3K/Akt pathway

Xiaofang Wei,
Juan Wang,
Yaqin Sun
et al.

Abstract: Numerous studies have revealed the profound impact of microRNAs on regulating skeletal muscle development and regeneration. However, the biological function and regulation mechanism of miR‐222‐3p in skeletal muscle remains largely unknown. In this study, miR‐222‐3p was found to be abundantly expressed in the impaired skeletal muscles, indicating that it might have function in the development and regeneration process of the skeletal muscle. MiR‐222‐3p overexpression impeded C2C12 myoblast proliferation and myog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…miRNAs are small non-coding RNAs that act as inhibitors of gene expression and play important roles in skeletal muscle development. Several miRNAs, including muscle-specific miRNAs such as those of the miR-1/miR-206 and miR-133a/miR-133b families [ 15 , 16 , 17 , 18 ], as well as miRNAs including miR-17 [ 19 ], miR-22 [ 20 ], miR-29 [ 21 ], miR-136 [ 20 ], miR-186 [ 22 ], miR-204 [ 23 ], and miR-222 [ 24 ], have been implicated in skeletal muscle development through their regulation of target genes. Muscle atrophy occurs when the rate of protein degradation exceeds protein synthesis, often induced by factors such as starvation and disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small non-coding RNAs that act as inhibitors of gene expression and play important roles in skeletal muscle development. Several miRNAs, including muscle-specific miRNAs such as those of the miR-1/miR-206 and miR-133a/miR-133b families [ 15 , 16 , 17 , 18 ], as well as miRNAs including miR-17 [ 19 ], miR-22 [ 20 ], miR-29 [ 21 ], miR-136 [ 20 ], miR-186 [ 22 ], miR-204 [ 23 ], and miR-222 [ 24 ], have been implicated in skeletal muscle development through their regulation of target genes. Muscle atrophy occurs when the rate of protein degradation exceeds protein synthesis, often induced by factors such as starvation and disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they found that and Ca 2+ can in uenceaffect the phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) pathway to alleviate pulmonary hypertension. TheMeanwhile, PI3K/Akt/mTOR signalling pathway is an important cellular transduction pathway in cells, thatwhich can promotes cell proliferation and differentiation, therebyus regulating cell growtWTh [20][21][22]. ThereforeBased on the above, wethis study aimed to establish and verify the effect of IRI on the expression of the PI3K/Akt/mTOR signalling pathway and apoptosis of skeletal muscle cells in the absence of the TRPC6 pathway in skeletal muscle.…”
mentioning
confidence: 99%